‘Internet+’ comprehensive nursing training course in the post-epidemic era—an exploration of the mixed teaching mode: a randomized trial - Wang, Qing-Ling; Liu, Lan-Lan; Liu, Cheng-Rui; Zhu, Qing-Shuang; Ren, Zhi-Ying; Gang, Ting-Ting; Zhou, Chun-Yan; Li, Qiu-Ping; Chen, Xi; Han, Bin-Ru (Frontiers in Medicine, 2023)
Objective: To explore the application effect of the ‘Internet+’ nursing teaching mode on the comprehensive training teaching ‘Fundamentals of Nursing’. Trial design: Parallel design and convenient sampling were used to select vocational nursing students from the Nursing College of Capital Medical University. Methods: Selected students were randomly divided into two groups. Thirty students in Grade 2020 higher vocational nursing education were the control group (traditional teaching mode), and 30 students in Grade 2021 higher vocational nursing education were the observation group (Internet+ mixed teaching mode). Training assessment results, automatic learning ability, professional identity and satisfaction were compared between the two groups. Results: Compared with the control group, the students in the observation group scored higher in the following operation practices: venous blood sampling, intradermal injections, cardiopulmonary resuscitation (CPR), sputum aspiration, and putting on and taking off robes (84.01 ± 0.87 vs 92.14 ± 1.23; 91.41 ± 0.82 vs 96.86 ± 0.27; 87.56 ± 0.31 vs 93.91 ± 2.79; 88.11 ± 0.51 vs 93.75 ± 0.29; 82.29 ± 0.29 vs 90.96 ± 0.34, respectively), (all P < 0.05). The total score of autonomous learning ability and subjective satisfaction was also higher in the observation group compared with the control group (82.98 ± 4.72 vs 93.17 ± 5.01; 96.67% vs 90.00%, respectively) (all P < 0.05). Conclusion: In the post-epidemic era, the ‘Internet+ hybrid teaching mode’ was applied to the comprehensive nursing training teaching. This changed the traditional education mode, which focuses only on professional knowledge. The ‘Internet+’ teaching mode results were that the professional and the ideological and political courses showed the same value guidance, which improved the students' independent learning ability and practical operation ability, increased their professional identity, and greatly improved their satisfaction.